2012
DOI: 10.1007/s00264-012-1742-z
|View full text |Cite
|
Sign up to set email alerts
|

Reverse shoulder arthroplasty in revision of failed shoulder arthroplasty—outcome and follow-up

Abstract: In revision shoulder arthroplasty after failed primary shoulder arthroplasty an inverse design can improve the functional outcome, and patient satisfaction is usually high. However, the complication rate of this procedure is also high, and patient selection and other treatment options should be carefully considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 40 publications
5
54
1
1
Order By: Relevance
“…Solutions for stem retention also need to be investigated. In our series, the complication and reoperation rates for patients who have had revision of a hemiarthroplasty or total shoulder to reverse total shoulder arthroplasty without the need for stem exchange compare favorably not only with rates of our control group, but also with reported results [20,21,23,26,33].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Solutions for stem retention also need to be investigated. In our series, the complication and reoperation rates for patients who have had revision of a hemiarthroplasty or total shoulder to reverse total shoulder arthroplasty without the need for stem exchange compare favorably not only with rates of our control group, but also with reported results [20,21,23,26,33].…”
Section: Discussionsupporting
confidence: 76%
“…Such revisions, however, are associated with the risk of intraoperative and/or postoperative complications [8,12,18,20,21,23,26,27,32,33]. Our study showed that revision of hemiarthroplasties or total-to reverse total shoulder arthroplasties performed without stem removal reduced operative time, blood loss, intraoperative complications, and reoperations compared with stem exchange.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Despite the widespread use of reverse total shoulder arthroplasty (RTSA) [1,11,27], the fundamental effects of implant configuration on certain biomechanical outcomes have not been completely elucidated. The deltoid muscle force required to produce active motion and the resulting joint load magnitude and angle throughout this motion are important factors when considering the potential effect of implant configuration on long-term RTSA performance.…”
Section: Introductionmentioning
confidence: 99%
“…Besides CTA, the indications for RSA include comminuted shoulder fractures, revisions, rheumatoid arthritis (RA) and severe osteoarthritis (OA) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%